Urinary stress incontinence and other maternal outcomes 2 years after caesarean or vaginal birth for twin pregnancy: a multicentre randomised trial - Hutton, EK (BJOG, 2018)
OBJECTIVE: Does planned caesarean compared with planned vaginal birth lower the risk of problematic urinary stress, faecal, or flatal incontinence? DESIGN: Women between 32(0/7) and 38(6/7) weeks of gestation with a twin pregnancy were randomised to planned caesarean or planned vaginal birth. SETTING: The trial took place at 106 centres in 25 countries. POPULATION: A total of 2305 of the 2804 women enrolled in the study completed questionnaires at 2 years (82.2% follow‐up): 1155 in the planned caesarean group and 1150 in the planned vaginal birth group. METHODS: A structured self‐administered questionnaire completed at 2 years postpartum. MAIN OUTCOME MEASURES: The primary maternal outcome of the Twin Birth Study was problematic urinary stress, or fecal, or flatal incontinence at 2 years RESULTS: Women in the planned caesarean group had lower problematic urinary stress incontinence rates compared with women in the planned vaginal birth group [93/1147 (8.11%) versus 140/1143 (12.25%); odds ratio, 0.63; 95% confidence interval, 0.47–0.83; P = 0.001]. Among those with problematic urinary stress incontinence, quality of life (measured using the Incontinence Impact Questionnaire, IIQ‐7) was not different for planned caesarean versus planned vaginal birth groups [mean (SD): 18.4 (21.0) versus 19.1 (21.5); P = 0.82]. There were no differences in problematic faecal or flatal incontinence, or in other maternal outcomes. CONCLUSIONS: Among women with a twin pregnancy and no prior history of urinary stress incontinence, a management strategy of planned caesarean compared with planned vaginal birth reduces the risk of problematic urinary stress incontinence at 2 years postpartum. Our findings show that the prevalence but not the severity of urinary stress incontinence was associated with mode of birth. FUNDING: Canadian Institutes of Health Research (CIHR) (grant no. MCT‐63164). TWEETABLE ABSTRACT: For women with twins, planned caesarean compared with planned vaginal birth is associated with decreased prevalence but not severity of urinary stress incontinence at 2 years.